Gene expression profile of duodenal epithelial cells in response to chronic metabolic acidosis - Kannikar Wongdee (2018)
Chronic metabolic acidosis (CMA) affects ion transport, permeability, and metabolism of the intestinal absorptive cells. Most effects of CMA on the intestine are long-term adaptations at genomic level. To identify the CMA-regulated genes, the Illumina's microarray featuring high-performance BeadArray technology was performed on RNA samples from the rat duodenal epithelial cells exposed to long-standing acidemia. After 21 days of CMA, we found 423 transcripts upregulated and 261 transcripts downregulated. Gene ontology analysis suggested effects of CMA on cellular processes, such as cell adhesion, proliferation, fuel metabolism, and biotransformation. Interestingly, 27 upregulated transcripts (e.g., Aqp1, Cacnb1, Atp1a2, Kcnab2, and Slc2a1) and 13 downregulated transcripts (e.g., Slc17a7, Slc9a4, and Slc30a3) are involved in the absorption of water, ions, and nutrients. Some upregulated genes, such as Slc38a5 and Slc1a7 encoding glutamine transporters, may be parts of the total body adaptation to alleviate negative nitrogen balance. Therefore, the present results provided a novel genome-wide information for further investigations of the mechanism of CMA effect on the intestine. © Springer Science+Business Media, LLC. 2008.